دراسة سوسيولوجية في رواية "الرهينة" لإميلي نصرالله - عمورى, نعيم; حسيني, زهرا سياحي (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Social critique is what deals with the connection between the artistic or literary work and the society in which it originated. This approach - social critique - is one of the main approaches in literary and critique studies. It links literature and society at different levels and analyzes the relationship between society and literature as a reflection of life. This research is based on a sociological study in the novel "The hostage" by Emily Nasrallah. The content of this novel focuses on the status of rural women, education, female bondage, and the status of the feudal system and its ruling on the lives of the participants. In her novel, the author attempts to show life in rural society and the injustice and disregard of women's status, where the Female from the time she was born and even before Belong to the farmer and the many interventions in their affairs and their life's destinies. The methodology of this study will be descriptive-analytical. يعالج النقد الاجتماعي الصلة بين العمل الفني أو الأدبي والمجتمع الذي نشأ فيه وهذا المنهج -أي النقد الاجتماعي-هو أحد المناهج الرئيسة في الدراسات الأدبية والنقدية وهو يربط بين الأدب والمجتمع في مختلف المستويات ويدرس علاقته ويحلله بإعتباره إِنعكاسا للحياة. يسعی هذا البحث إلی دراسة سوسيولوجية في رواية الرهينة للكاتبة إميلي نصرالله ويترکز مضمون هذه الرواية علی وضع المرأة الريفية، والتعليم، ورهن الأنثی، وسطوة النظام الإقطاعي وتحکّمه في حياة التابعين. تحاول الکاتبة‌ في هذه الرواية أن تبين الحياة في المجتمع الريفي وما يدور فيه من ظلم واستهانة لمکانة المرأة حيث تَرتَهنُ الأنثی منذ صغر سنها وحتی قبل أن تولد لصاحب المزارع وکثرة تدخلاته في أمورها الحياتية ومصيرها. سندرس هذه الرواية متبعين المنهج الوصفي في التحليل والدراسة.